Pharmacy practice guide to compounding and dispensing / Shariza Sahudin, Rudy Rabi, Ng Shiow Fern, Thomas Paraidathathu - Shariza Sahudin; Rudy Rabi; Ng, Shiow Fern; Thomas Paraidathathu (Penerbit Universiti Kebangsaan Malaysia, 2011)
[This book] is designed to guide students and practitioners in the compounding and dispensing of extemporaneous preparations.